Um estudo sobre os conhecimentos de educandos em um curso técnico de edificações - Santos, Viviane Fernandes (2020)
This work presents a qualitative study based on the researcher's teaching action, developed with 20 students from a class of the 1st year of the Integrated Building Course for High School, in the discipline of Study of Soil and Materials in Civil Construction (ESMCC), aged 14 to 17 years. For this, we conducted a case study that begins with a documentary analysis of the ESMCC discipline program to identify the scientific knowledge related to basic mathematics, necessary for the development of the discipline. Based on the data collected, we developed and applied the evaluation instrument to 20 participants, in order to identify the degree of mastery that these students have in relation to the concepts of Quantities and Measures, related to the calculation of area, volume and conversion of units of measures . These concepts are prerequisites, among others, considered important for the development of the subject in focus. To form our theoretical contribution, we look at the laws and studies on Technical Education Integrated to High School, as well as the guidelines established for its operation in the Building Course Plan. We adopted the proposal by CURY (2018), to analyze errors made by the research participants, in the tasks to be solved. The results of the research show that the participants have a level of mastery below what was expected in their current schooling phase, which interferes with the development of the contents of the technological bases of the discipline. The main errors found are related to the lack of mastery of concepts in quantities and measures, difficulties in the development of multiplication and division operations, and especially in the manipulation with decimal numbers.